2016
DOI: 10.4103/0972-5229.188191
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of pneumothorax among patients admitted to a Pediatric Intensive Care Unit

Abstract: Objective:Pneumothorax should be considered a medical emergency and requires a high index of suspicion and prompt recognition and intervention.Aims:The objective of the study was to evaluate cases developing pneumothorax following admission to a Pediatric Intensive Care Unit (PICU) over a 5-year period.Settings and Design:Case notes of all PICU patients (n = 1298) were reviewed, revealing that 135 cases (10.4%) developed pneumothorax, and these were compared with those patients who did not. The most common too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
(38 reference statements)
2
11
2
Order By: Relevance
“…Therefore, it is not appropriate to compare these studies with results of the current study. In contrast to these data a study from India reported a 10.4% prevalence rate of pneumothorax in PICU patients (21), which was very high compared to reported rate of 4.4% in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is not appropriate to compare these studies with results of the current study. In contrast to these data a study from India reported a 10.4% prevalence rate of pneumothorax in PICU patients (21), which was very high compared to reported rate of 4.4% in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study reported by Silva and colleagues; duration of MV, PICU and hospital stays were similar between both groups (18). In a study evaluating 1238 pediatric patients admitted to PICU, those with pneumothorax had higher mortality rate (P < 0.001), and longer duration of hospitalization (P < 0.001) (21). Similar to our study ventilated patients who developed pneumothorax had a longer duration of mechanical ventilation compared with ventilated patients without pneumothorax (P < 0.001) (21).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…While five patients underwent tube thoracostomy, all patients received oxygen therapy with 100% FiO 2 until pneumothorax ameliorated. In a study, it has been established that length of intensive care unit stay and mortality increased in patients developing pneumothorax out of 1238 pediatric patients admitted to the intensive care unit (22). Although it was seen that length of intensive care unit stay of the cases with SP secondary to viral pneumonia was longer than that of pneumonia cases who did not develop pneumothorax in our center, a comparison could not be made because of the small sample size.…”
Section: Discussionmentioning
confidence: 83%